Enhancing English proficiency through social circle and vocabulary among Malaysian adult learners - Astri Yulia; R. Malatesha Joshi; Nor Azilah Husin; Sakhiyyah A. Rahim (Studies in English Language and Education, 2023)
For second language learners, language proficiency is normally gained through formal instructions in the English as a second language classroom. However, besides the classroom, language can also be learned in a natural setting, for example, through social interactions. This study examines social interaction as an alternative approach to improving English language proficiency. A total of 93 students participated in the study. Sixty of the students were from the school of education, and 38 were from a private university. The participants took an Online English level and vocabulary test as part of data collection of this study. The data analysis was conducted using two multiple regression models in SPSS version 22. The multiple regressions yielded a correlational report between the social circle and English language proficiency among the students. Results demonstrated that the students’ social circle was close (M=60). These variables are not critical when accounting for social and close circles independently in a regression model. Only vocabulary was detected as a significant factor influencing the students’ English proficiency. However, the interaction between the social circle and vocabulary positively contributes to English proficiency. This finding supports the social capital in which learning can be enhanced through social interactions within a social circle. Furthermore, this finding calls for teachers’ and education practitioners’ attention to facilitate vocabulary learning through social interactions.